2016
DOI: 10.1002/ajmg.b.32423
|View full text |Cite
|
Sign up to set email alerts
|

A pilot integrative genomics study of GABA and glutamate neurotransmitter systems in suicide, suicidal behavior, and major depressive disorder

Abstract: Gamma-amino butyric acid (GABA) and glutamate are the major inhibitory and excitatory neurotransmitters in the mammalian central nervous system, respectively, and have been associated with suicidal behavior and major depressive disorder (MDD). We examined the relationship between genotype, brain transcriptome, and MDD/suicide for 24 genes involved in GABAergic and glutamatergic signaling. In part 1 of the study, 119 candidate SNPs in 24 genes (4 transporters, 4 enzymes, and 16 receptors) were tested for associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 67 publications
3
36
0
2
Order By: Relevance
“…We found that Gabarapl1 expression was increased by chronic stress in the PFC and NAc, consistent with results in human MDD in which expression is increased in Brodmann area 9 (BA9), BA10, BA20, and BA46 [84, 85]. Consistent with what we observed for the effects of stress on Gabra2 expression in the PFC and NAc, subjects with MDD have increased Gabra2 expression in the cerebellum [86].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that Gabarapl1 expression was increased by chronic stress in the PFC and NAc, consistent with results in human MDD in which expression is increased in Brodmann area 9 (BA9), BA10, BA20, and BA46 [84, 85]. Consistent with what we observed for the effects of stress on Gabra2 expression in the PFC and NAc, subjects with MDD have increased Gabra2 expression in the cerebellum [86].…”
Section: Discussionsupporting
confidence: 88%
“…Our results for Gria1 are consistent with reports in the literature. For instance, GRIA1 expression is increased in BA9 [84, 87] and BA21 [85] in MDD subjects. We also saw increased Gria1 expression in the PFC and NAc of chronically stressed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine and immune system interactions play an important role in stress response (Ashley & Demas, 2017;Dantzer, 2018). By comparing our results with that of a meta-analysis on genes implicated in MDD (Gatt et al, 2015;Manoharan et al, 2016;Yin et al, 2016), we found that most of the pathways reported earlier were also identified in the current study. Both stress and inflammatory cytokine activation have been reported to have adverse effect on the neurogenesis and neural plasticity (Syed et al, 2018).…”
Section: Ta B L E 1 (Continued)supporting
confidence: 71%
“…Although twin studies have documented genetic influences on suicide-related phenotypes (heritability ~30% – 55%) [Tidemalm et al 2011], it is clear that suicidality is a multi-determined, genetically complex trait, as is the case for virtually all mental and behavioral disorders [Gelernter 2015]. Thus, a great many genes and genomic processes (e.g., epistasis and epigenetic variation) are likely to contribute to risk for suicidality, but none have been firmly established [Niculescu et al 2015a; Oquendo et al 2014; Sokolowski et al 2014; Turecki 2014; Yin et al 2016]. …”
Section: Introductionmentioning
confidence: 99%